Whippoorwill - Monninger, Joseph (Houghton Mifflin Harcourt, 2016)
Clair Taylor's neighbors are whippoorwills, the kind of people who don't mind filling their property with rusted car parts and broken furniture. When the neighbors add a sweet black dog named Wally to the junk pile, all chained up, Clair cannot look the other way. Surprisingly, neither can Danny Stewart, a boy whose family is dark with violence. Clair and Danny take it upon themselves to save Wally, and give everyone a second chance.